(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Structural audit is an overall health and performance check-up of building .It is important to the building to check their safety and they have no risk. It is process of analyses of building And this process suggest a appropriate repairs and retrofitting measures required for the building to perform better in its service life, structural audit is an important tool for knowing the real status of the old building. Currently, safety of old buildings which is present in heavy rainfall area is one of the critical issues in India though, there are many practises to conduct structural audit of such buildings. The need of structural audit is for maintenance and repairs of existing structure whose life has exceeded the age of 30 years to avoid mishaps and save valuable human life. The concrete is widely used as construction material being inexpensive, easy for construction, application and because of it high strength-cost ratio. More than ever, the construction industry is concerned with improving the social, economic and environmental parameters of sustainability.